Front Cover: Synergistic Effects of Surface Coating and Bulk Doping in Ni‐Rich Lithium Nickel Cobalt Manganese Oxide Cathode Materials for High‐Energy Lithium Ion Batteries (ChemSusChem 4/2022). Issue 4 (1st February 2022) - Reissig, Friederike; Lange, Martin Alexander; Haneke, Lukas; Placke, Tobias; Zeier, Wolfgang G.; Winter, Martin; Schmuch, Richard; Gomez‐Martin, Aurora
Abstract : The Front Cover shows multiple treatment choices for the modification of cathode active materials for lithium‐ion batteries. Like for a car wash program, the treatment will typically result in an improvement of the status quo. However, the best treatment procedure will only become clear if all options are explored. In the present work, this means to not only investigate various coated samples, but also samples modified via the same heat‐treatment without coating. More information can be found in the Research Article by Friederike Reissig et al .